Method for producing wet sheet
Patent Information
- Application Number
- JP2023136254
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0008】 本発明の製造方法により、ウェットシートの製造工程における断紙を防止することができる。本発明の製造方法は、生産速度を速くしても断紙が起こりにくいため、生産性を高めることができる。 本発明の製造方法は、搬送中の基材シートにセルロースナノファイバーを含む塗工液を噴霧するが、ウェット塗工量が少ないため乾燥が容易であり、搬送中に自然乾燥も可能である。
Smart Images

Figure 2025030717000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a wet wipe. [Background technology]
[0002] Known wet sheets include cleaning wet sheets for cleaning floors, toilets, etc., body wiping wet sheets for wiping off sweat and dirt from infants and those receiving care, and cosmetic wet sheets soaked in lotion or milky lotion.
[0003] Such various wet wipes are generally manufactured by folding a long base sheet with a folding plate or a holding machine while being transported, cutting it to a product size, stacking it, and impregnating it with a chemical solution according to its purpose.For example, Patent Document 1 proposes a manufacturing method for a nonwoven fabric sheet that can suppress the generation of paper dust and prevent the fusion of fibers, including a step of unwinding base paper from a base roll, a step of folding the base paper in half in the flow direction by a folding process using a folding plate, a step of folding the folded base paper in the width direction by a folding process using a folding roll, a step of cutting the center of the folded base paper with a band saw, a step of cooling the band saw, and a step of collecting paper dust with a dust collector.
[0004] Here, the base sheet used in the wet wipes has a low basis weight because it is required to have many voids so that it can hold a large amount of chemical solution. A low basis weight base sheet has low strength, so it is prone to breakage starting from the point of contact with the folding plate, and is also prone to breakage because the base sheet is pulled strongly when folded by the holding machine. Wet wipes are manufactured at slow line speeds to reduce the load placed on them during the folding process and prevent breaks, so there was a demand for improved productivity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-115262 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a method for producing a wet wipe that is less likely to break. [Means for solving the problem]
[0007] The means for solving the problems of the present invention are as follows. 1. A coating solution containing 0.1% to 3.0% by mass of cellulose nanofibers with an average fiber length of 450 nm or less is applied to a long substrate sheet at a wet coating amount of 0.1 g / m 2 More than 5.0g / m 2 A spraying step of spraying the following: a drying step of drying the base sheet after the spraying step; A folding process step of folding the base sheet after the drying process; A method for producing a wet wipe, comprising the steps of: 2. The method for producing wet wipes according to 1., wherein the base sheet is a nonwoven fabric. 3. The method for producing a wet wipe according to 1 or 2, characterized in that the drying is natural drying. 4. The method for producing a wet wipe according to any one of 1. to 3., wherein the cellulose nanofiber is an oxidized cellulose nanofiber. Effect of the Invention
[0008] The manufacturing method of the present invention can prevent sheet breaks during the manufacturing process of wet wipes. The manufacturing method of the present invention can increase productivity because sheet breaks are unlikely to occur even when the production speed is increased. In the manufacturing method of the present invention, a coating liquid containing cellulose nanofibers is sprayed onto a base sheet while it is being transported. Since the amount of wet coating is small, drying is easy and natural drying is also possible while the sheet is being transported. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Base sheet The substrate sheet can be any substrate usable for wet wipes without any particular limitations. Examples of the substrate sheet include nonwoven fabric and paper, with nonwoven fabric being preferred from the standpoint of strength. Examples of raw fiber for the base sheet include one or more of the following: cellulosic fibers such as wood pulp, non-wood pulp, rayon, and cotton; synthetic fibers such as polyester fibers, polyacrylonitrile fibers, polyethylene fibers, polypropylene fibers, polyvinyl alcohol fibers, polylactic acid fibers, polybutylene succinate adipate fibers, polybutylene succinate fibers, polycaprolactone fibers, and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) fibers; and inorganic fibers such as glass wool. Among these, cellulosic fibers and biodegradable synthetic fibers are preferred because they have less adverse impact on the environment when they are disposed of as waste.
[0010] The base sheet may be water-disintegrable or non-water-disintegrable, and if it is water-disintegrable, it can be disposed of by flushing it down a toilet after use. Water-disintegrable means that the floc water dispersion time (300 ml of deionized water is placed in a 300 ml beaker, one 3 cm square test piece is placed in while stirring with a stirrer at 650 rpm, and the time it takes for the test piece to break into two or more pieces) is within 30 seconds.
[0011] The base sheet can be obtained by a known method for producing nonwoven fabric or paper. As the nonwoven fabric, a spunlace nonwoven fabric is preferable because it does not contain an adhesive and is therefore highly safe for use on the human body, and because it has many voids between the fibers and can contain a large amount of chemical solution. The base sheet has a basis weight of 20 g / m 2 More than 60g / m 2 From the viewpoint of the balance between strength, light weight, and amount of impregnated chemicals, it is preferable that the base sheet has a basis weight of 23 g / m or less. 2 More preferably, 26 g / m 2More preferably, 56 g / m 2 Less than 52 g / m is more preferable. 2 The following is even more preferred:
[0012] Cellulose nanofiber Cellulose nanofibers (hereinafter, also referred to as CNF) are fine fibers obtained by subjecting cellulose raw materials such as pulp to chemical modification or other treatments as necessary, followed by defibration treatment. The fiber width (average fiber diameter) of CNF is usually about 3 nm to several hundred nm, for example, about 3 to 500 nm. The CNF used in the present invention has an average fiber length of 450 nm or less. In the present invention, by using CNF with an average fiber length of 450 nm or less, clogging of the spraying device is unlikely to occur, and the diameter of the sprayed droplets can be reduced by reducing the nozzle diameter. Furthermore, the small droplets facilitate drying and allow the CNF to be uniformly attached within the surface of the base sheet.
[0013] The average fiber length of the CNF is preferably 400 nm or less, more preferably 350 nm or less. There is no particular lower limit to the average fiber length, but in order to obtain the effect of improving the strength of the base sheet by the CNF, it is preferably 100 nm or more, more preferably 150 nm or more. In addition, the CNF used in the present invention has a number ratio of CNFs having a length of 600 nm or more of preferably 10% or less, more preferably 5% or less, even more preferably 3% or less, and even more preferably 1% or less. The CNF of the present invention preferably has an average fiber diameter of 3 nm or more and 100 nm or less, and more preferably 20 nm or less.
[0014] The average fiber length and average fiber diameter of CNF can be obtained by calculating the average fiber length and fiber diameter obtained from the observation of approximately 200 fibers using an atomic force microscope (AFM) or a transmission electron microscope (TEM), and specifically, can be determined by the following measurement method. <Number average fiber diameter> A CNF aqueous dispersion is prepared by diluting the CNF to a concentration of 0.001% by mass. This aqueous dispersion is thinly spread on a mica sample stage and dried by heating at 50°C to prepare a sample for observation. The cross-sectional heights of at least 30 random fibers in the shape images observed with an atomic force microscope (AFM) are measured, and the number-average fiber diameter is calculated. <Number average fiber length> From the atomic force microscope image (3000 nm × 3000 nm) of the CNF fixed on the mica slice, the fiber length of 30 or more random fibers is measured and the number average fiber length is calculated. The fiber length is measured in the length range of 10 nm to 2000 nm using the image analysis software WinROOF (Mitani Corporation).
[0015] CNF can be obtained by applying mechanical force to a cellulose raw material such as pulp described later to pulp and thereby pulverizing (fibrillating). As the cellulose raw material, unmodified cellulose or pulp for papermaking, etc., as described later, may be used, or chemically modified cellulose obtained by further chemically modifying pulp for papermaking, etc., may be used. Examples of chemically modified cellulose include, but are not limited to, anion-modified cellulose in which an anionic group is introduced into the cellulose chain, and cation-modified cellulose in which a cationic group is introduced. Among these, anion-modified cellulose is preferably used because it is easy to obtain CNF with a short fiber length. In particular, among anion-modified cellulose, carboxylated cellulose (oxidized cellulose) in which a carboxy group is introduced as an anionic group is suitable as a raw material for CNF used in the present invention.
[0016] (Cellulose raw material) Cellulose as a raw material for CNF is known to originate from plants, animals (e.g., ascidians), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc., and any of them can be used in the present invention. Examples of plant-derived cellulose include wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, and pulp (softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.). In the present invention, cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred. The cellulose raw material may be chemically modified as described below. CNF or chemically modified CNF can be obtained by miniaturizing the fiber width of the above-mentioned cellulose raw material or chemically modified cellulose raw material (chemically modified cellulose) to the nanometer level.
[0017] (Chemically modified cellulose) Examples of chemically modified cellulose include, but are not limited to, anion-modified cellulose in which an anionic group is introduced into the cellulose chain, and cation-modified cellulose in which a cationic group is introduced. Examples of anion-modified cellulose include carboxylated cellulose in which a carboxy group is introduced, carboxymethylated cellulose in which a carboxymethyl group is introduced, and phosphate-modified cellulose in which a phosphate group or the like is introduced. Among these, it is preferable to use anion-modified cellulose, and it is also preferable to use carboxylated cellulose.
[0018] (Carboxylated Cellulose) An example of anion-modified cellulose is carboxylated (oxidized) cellulose (carboxylated cellulose). Carboxylated cellulose can be obtained by carboxylating (oxidizing) the above-mentioned cellulose raw material by a known method. Although not particularly limited, during carboxylation, the amount of carboxy groups is preferably adjusted to 0.6 to 3.0 mmol / g, more preferably adjusted to 0.6 to 2.0 mmol / g, and even more preferably adjusted to 1.0 mmol / g to 2.0 mmol / g, based on the bone dry mass of the carboxylated cellulose.
[0019] An example of the carboxylation (oxidation) method is a method in which a cellulose raw material is oxidized in water using an oxidizing agent in the presence of an N-oxyl compound and a compound selected from the group consisting of bromides, iodides, or a mixture thereof. This oxidation reaction selectively oxidizes the primary hydroxyl group at the C6 position of the glucopyranose ring on the cellulose surface, and produces cellulose having an aldehyde group and a carboxy group (-COOH) or a carboxylate group (-COO-) on the surface. The concentration of the cellulose raw material during the reaction is not particularly limited, but is preferably 5% by mass or less.
[0020] The term "N-oxyl compound" refers to a compound capable of generating a nitroxy radical. Any compound that can promote the desired oxidation reaction can be used as the N-oxyl compound. For example, 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO) and its derivatives (e.g., 4-hydroxyTEMPO) can be mentioned. The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the raw cellulose. For example, the amount is preferably 0.01 to 10 mmol, more preferably 0.01 to 1 mmol, and even more preferably 0.05 to 0.5 mmol per 1 g of bone dry cellulose. Also, the amount is preferably about 0.1 to 4 mmol / L relative to the reaction system.
[0021] Bromides are compounds containing bromine, examples of which include alkali metal bromides that can dissociate and ionize in water. Also, iodides are compounds containing iodine, examples of which include alkali metal iodides. The amount of bromide or iodide used can be selected within a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 to 100 mmol, more preferably 0.1 to 10 mmol, and even more preferably 0.5 to 5 mmol, per 1 g of bone-dry cellulose.
[0022] The oxidizing agent may be a known one, such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxide, peroxide, etc. Among them, sodium hypochlorite is preferable because it is inexpensive and has a low environmental impact. The amount of the oxidizing agent used is preferably 0.5 to 500 mmol, more preferably 0.5 to 50 mmol, even more preferably 1 to 25 mmol, and most preferably 3 to 10 mmol, per 1 g of bone-dry cellulose raw material. Also, for example, 1 to 40 mol is preferable per 1 mol of the N-oxyl compound.
[0023] The oxidation of cellulose can proceed efficiently even under relatively mild conditions. Therefore, the reaction temperature is preferably 4 to 40°C, or may be room temperature of about 15 to 30°C. As the reaction proceeds, carboxyl groups are generated in the cellulose, and a decrease in the pH of the reaction solution is observed. In order to efficiently proceed with the oxidation reaction, it is preferable to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at about 8 to 12, preferably 10 to 11. The reaction medium is preferably water, because it is easy to handle and does not easily cause side reactions.
[0024] The reaction time in the oxidation reaction can be appropriately set according to the degree of progress of the oxidation, and is usually from 0.5 to 6 hours, for example, about 0.5 to 4 hours. The oxidation reaction may be carried out in two stages. For example, the carboxylated cellulose obtained by filtering after the first stage reaction can be oxidized again under the same or different reaction conditions, allowing efficient oxidation without reaction inhibition by table salt produced as a by-product in the first stage reaction.
[0025] Another example of the carboxylation (oxidation) method is a method in which the cellulose raw material is oxidized by contacting an ozone-containing gas with the raw material. This oxidation reaction oxidizes (carboxylates) at least the 2- and 6-hydroxyl groups of the glucopyranose ring, and decomposes the cellulose chain. The ozone concentration in the ozone-containing gas is 50 to 250 g / m 3 It is preferable that the thickness is 50 to 220 g / m 3 It is more preferable that the ozone is added to the cellulose raw material in an amount of 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass, based on 100 parts by mass of the solid content of the cellulose raw material. The ozone treatment temperature is preferably 0 to 50°C, and more preferably 20 to 50°C. The ozone treatment time is not particularly limited, but is about 1 to 360 minutes, and is preferably about 30 to 360 minutes. When the ozone treatment conditions are within these ranges, it is possible to prevent cellulose from being excessively oxidized and decomposed, and the yield of carboxylated cellulose is good. After the ozone treatment, an oxidizing agent may be used to perform a post-oxidation treatment. The oxidizing agent used in the post-oxidation treatment is not particularly limited, but examples thereof include chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. For example, these oxidizing agents are dissolved in a polar organic solvent such as water or alcohol to prepare an oxidizing agent solution, and the cellulose raw material is immersed in the solution to perform the post-oxidation treatment.
[0026] The amount of carboxy groups in carboxylated cellulose can be adjusted by controlling reaction conditions such as the amount of oxidizing agent added, reaction time, etc. The amount of carboxy groups in carboxylated cellulose is usually the same as the amount of carboxy groups in carboxylated CNF obtained by defibrating the carboxylated cellulose. Carboxylated CNF can be produced by defibrating carboxylated cellulose using the method described below.
[0027] (Carboxymethylcellulose) An example of anion-modified cellulose is carboxymethylated cellulose (hereinafter, carboxymethylation is referred to as "carboxymethylation"). The carboxymethylated cellulose may be obtained by carboxylizing the above-mentioned cellulose raw material by a known method, or a commercially available product may be used. In either case, the degree of carboxymethyl group substitution per anhydrous glucose unit of cellulose is preferably 0.01 to 0.50. An example of a method for producing such carboxymethylated cellulose is as follows. To the cellulose raw material, 3 to 20 times by mass of water and / or a lower alcohol, specifically, water, methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, isobutanol, tertiary butanol, etc., are added as a solvent, or a mixture of two or more of them. When a lower alcohol is mixed, the mixing ratio of the lower alcohol is preferably 60 to 95% by mass. As the mercerizing agent, it is preferable to use 0.5 to 20 times by mole of an alkali metal hydroxide, specifically, sodium hydroxide or potassium hydroxide, per anhydrous glucose residue of the cellulose raw material. The cellulose raw material, solvent, and mercerizing agent are mixed, and a mercerization treatment is carried out at a reaction temperature of 0 to 70° C., preferably 10 to 60° C., for a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Then, a carboxymethylating agent is added at 0.05 to 10.0 times the moles per glucose residue, and an etherification reaction is carried out at a reaction temperature of 30 to 90° C., preferably 40 to 80° C., for a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.
[0028] In this specification, "carboxymethylated cellulose" or "CM-modified cellulose", which is a type of anion-modified cellulose used in the preparation of CM-CNF, refers to a type that maintains at least a part of its fibrous shape even when dispersed in water. Therefore, "carboxymethylated cellulose" or "CM-modified cellulose" is distinguished from carboxymethyl cellulose, which is a type of water-soluble polymer. When an aqueous dispersion of "carboxymethylated cellulose" or "CM-modified cellulose" is observed with an electron microscope, a fibrous substance can be observed. On the other hand, when an aqueous dispersion of carboxymethyl cellulose, which is a type of water-soluble polymer, is observed, no fibrous substance is observed. In addition, when "carboxymethylated cellulose" or "CM-modified cellulose" is measured by X-ray diffraction, a peak of cellulose type I crystals can be observed, but cellulose type I crystals are not observed in carboxymethyl cellulose, a water-soluble polymer.
[0029] Carboxymethylated cellulose can be defibrated by the method described below to produce carboxymethylated CNF. Note that the degree of carboxymethyl substitution in carboxymethylated cellulose is usually the same as the degree of carboxymethyl substitution in carboxymethylated CNF obtained by defibrating the same carboxymethylated cellulose.
[0030] (Cellulose phosphate) An example of anion-modified cellulose is phosphated cellulose, which can be obtained by mixing the above-mentioned cellulose raw material with a powder or an aqueous solution of a phosphoric acid compound.
[0031] Examples of phosphoric acid compounds include phosphoric acid, polyphosphoric acid, phosphorous acid, phosphonic acid, polyphosphonic acid, metaphosphoric acid, pyrophosphoric acid, or salts or esters thereof. Among these, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium metaphosphate, and the like are preferred because of their low cost, ease of handling, and improved defibration efficiency, and phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are more preferred. Sodium dihydrogen phosphate and disodium hydrogen phosphate are particularly preferred. These can be used alone or in combination of two or more. In addition, the phosphoric acid compound is preferably used as an aqueous solution because it enhances the uniformity of the reaction and increases the efficiency of phosphoric acid group introduction. The pH of the aqueous solution of the phosphoric acid compound is preferably 7 or less because it increases the efficiency of phosphoric acid group introduction, and is preferably pH 3 to 7 from the viewpoint of suppressing hydrolysis of cellulose fibers.
[0032] The following method can be given as an example of a method for producing phosphated cellulose. A phosphoric acid compound is added to a dispersion of a cellulose raw material having a solid content concentration of 0.1 to 10% by mass while stirring to introduce a phosphoric acid group into the cellulose. When the cellulose raw material is taken as 100 parts by mass, the amount of the phosphoric acid compound added is preferably 0.2 to 500 parts by mass, more preferably 1 to 400 parts by mass, in terms of the amount of phosphorus element. If the proportion of the phosphoric acid compound is equal to or greater than the lower limit, the yield of phosphoric acid-esterified CNF can be further improved. However, if the upper limit is exceeded, the effect of improving the yield reaches a plateau, which is not preferable from the viewpoint of cost.
[0033] In addition to the cellulose raw material and the phosphoric acid compound, a nitrogen-containing compound exhibiting basicity may be added. Here, "basicity" is defined as an aqueous solution exhibiting pink to red color in the presence of a phenolphthalein indicator, or an aqueous solution having a pH of more than 7. Examples of the nitrogen-containing compound exhibiting basicity include, but are not limited to, compounds having an amino group. For example, urea, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine are included. Among these, urea, which is low-cost and easy to handle, is preferred. The amount of the nitrogen-containing compound exhibiting basicity to be added is preferably 2 to 1000 parts by mass, more preferably 100 to 700 parts by mass, relative to 100 parts by mass of the solid content of the cellulose raw material. The reaction temperature is preferably 0 to 95°C, more preferably 30 to 90°C. The reaction time is not particularly limited, but is about 1 to 600 minutes, more preferably 30 to 480 minutes. When the phosphorylation reaction conditions are within these ranges, it is possible to prevent cellulose from being excessively esterified and becoming easily soluble, and the yield of phosphorylated cellulose is good. After the obtained phosphorylated cellulose suspension is dehydrated, it is preferable to heat treat it at 100 to 170°C from the viewpoint of suppressing hydrolysis of cellulose. Furthermore, it is preferable to heat it at 130°C or less, preferably 110°C or less while it contains water during the heat treatment, and after removing the water, heat treat it at 100 to 170°C.
[0034] The degree of phosphate substitution per glucose unit of the phosphated cellulose is preferably 0.001 to 0.40. By introducing a phosphate group substituent into cellulose, the celluloses are electrically repelled from each other. Therefore, cellulose into which a phosphate group has been introduced can be easily defibrated to a nanoscale fiber width. If the degree of phosphate substitution per glucose unit is less than 0.001, it cannot be sufficiently defibrated to a nanoscale. On the other hand, if the degree of phosphate substitution per glucose unit is more than 0.40, it may swell or dissolve, and therefore it may not be possible to obtain it as CNF. In order to perform defibration efficiently, it is preferable to boil the phosphated cellulose obtained above and then wash it with cold water.
[0035] Phosphated CNF can be produced by defibrating phosphated cellulose using the method described below. Note that the degree of phosphate substitution in the phosphated CNF is usually the same as the degree of phosphate substitution in the phosphated CNF obtained by defibrating the same phosphated cellulose.
[0036] (cationically modified cellulose) The chemically modified cellulose used in the preparation of chemically modified CNF may be cationically modified cellulose obtained by further cationizing the carboxylated cellulose. The cationically modified cellulose can be obtained by reacting the carboxylated cellulose with a cationizing agent such as glycidyl trimethylammonium chloride, 3-chloro-2-hydroxypropyl trialkylammonium hydrite or its halohydrin type, and an alkali metal hydroxide catalyst (sodium hydroxide, potassium hydroxide, etc.) in the presence of water or an alcohol having 1 to 4 carbon atoms.
[0037] The degree of cationic substitution per glucose unit is preferably 0.02 to 0.50. By introducing cationic substituents into cellulose, the celluloses are electrically repelled from each other. Therefore, cellulose into which cationic substituents have been introduced can be easily defibrated to nanoscale fiber widths. If the degree of cationic substitution per glucose unit is less than 0.02, it cannot be defibrated sufficiently. On the other hand, if the degree of cationic substitution per glucose unit is more than 0.50, it may swell or dissolve, making it impossible to obtain CNF. In order to perform defibration efficiently, it is preferable to wash the cationically modified cellulose obtained above before defibration. The degree of cationic substitution can be adjusted by the amount of cationizing agent to be reacted and the composition ratio of water or alcohol having 1 to 4 carbon atoms.
[0038] Cationically modified CNF can be produced by fibrillating cationically modified cellulose using the method described below. Note that the degree of cationic substitution in the cationically modified cellulose is usually the same as the degree of cationic substitution in the cationically modified CNF obtained by fibrillating the same cationically modified cellulose.
[0039] (Defibrilization) CNF can be obtained by defibrating the cellulose raw material containing the above-mentioned chemically modified cellulose. The device used for defibration is not particularly limited, but it is preferable to use a high-speed rotation type, colloid mill type, high-pressure type, roll mill type, ultrasonic type, cavitation type, or other device capable of applying a strong shear force. In particular, for efficient defibration, it is preferable to use a wet high-pressure or ultra-high-pressure homogenizer that applies a pressure of 50 MPa or more to the dispersion liquid of the cellulose raw material to be subjected to defibration and can apply a strong shear force. The pressure is more preferably 100 MPa or more, and even more preferably 140 MPa or more. In addition, prior to the defibration and dispersion treatment with the high-pressure homogenizer, a pretreatment may be performed using a known mixing, stirring, emulsifying, and dispersing device such as a high-speed shear mixer, as necessary. The average fiber length of CNF obtained by defibration can be adjusted by changing defibration conditions such as the type of equipment and pressure, as well as the combination of preliminary treatments.
[0040] (Coating fluid containing CNF) The above defibration process results in a dispersion containing CNF, which can be used as a coating liquid either as is or after dilution or solvent replacement. The dispersion medium of the coating liquid is not particularly limited, and may be water, a hydrophilic organic solvent, a hydrophobic organic solvent, or a mixed solvent thereof, with water or a mixed solvent of water and a hydrophilic organic solvent being preferred. The hydrophilic organic solvent means an organic solvent that is compatible with water, and examples thereof include methanol, ethanol, 2-propanol, butanol, glycerin, acetone, methyl ethyl ketone, 1,4-dioxane, N-methyl-2-pyrrolidone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile, and combinations thereof. Among these, lower alcohols having 1 to 4 carbon atoms such as methanol, ethanol, and 2-propanol are preferred, and from the viewpoints of safety and availability, methanol and ethanol are more preferred, and ethanol is even more preferred.
[0041] Since most chemically modified celluloses are produced using water as a dispersion medium, when using chemically modified CNF derived from chemically modified celluloses such as anionically modified cellulose or carboxylated cellulose, the aqueous dispersion of chemically modified CNF obtained by defibrating the chemically modified cellulose can be used as the coating liquid either as is or by adding a hydrophilic organic solvent. When using a mixed solvent of water and a hydrophilic organic solvent, the hydrophilic organic solvent may be added to an aqueous dispersion of a cellulose raw material such as chemically modified cellulose or an aqueous dispersion of CNF, or a part of the aqueous dispersion may be replaced with a hydrophilic organic solvent. The amount of the hydrophilic organic solvent in the mixed solvent is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on the mass of the mixed solvent. The upper limit of the amount of the hydrophilic organic solvent in the mixed solvent is not limited, but is preferably 95% by mass or less, and more preferably 80% by mass or less. The mixed solvent may also contain a hydrophobic organic solvent to the extent that the effect of the invention is not impaired.
[0042] "Wet Sheet Manufacturing Method" The method for producing the wet wipe of the present invention comprises the steps of: A coating solution containing 0.1% to 3.0% by mass of cellulose nanofibers with an average fiber length of 450 nm or less is applied to a long substrate sheet at a wet coating rate of 0.1 g / m 2 More than 5.0g / m 2 A spraying step of spraying the following: a drying step of drying the base sheet after the spraying step while transporting it; A folding process of folding the dried base sheet after the drying process; has.
[0043] ·Spraying process A coating solution containing 0.1% by mass to 3.0% by mass of cellulose nanofibers with an average fiber length of 450 nm or less was applied to a long substrate sheet obtained by a known method in a wet coating amount of 0.1 g / m 2 More than 5.0g / m 2 Spray with: The smaller the wet coating weight of the coating liquid, the easier it is to dry. Therefore, the wet coating weight was set at 4.0 g / m 2 Less than 3.0 g / m is preferred. 2 Less than 2.0 g / m is more preferable. 2 More preferably, 1.0 g / m 2 Even more preferably, 0.5 g / m 2 Even more preferred is the following:
[0044] The coating liquid contains 0.1% by mass or more and 3.0% by mass or less of CNF with an average fiber length of 450 nm or less. If the amount of CNF in the coating liquid exceeds 3.0% by mass, the coating liquid becomes highly viscous, making it difficult to spray uniformly or in small droplets. The amount of CNF in the coating liquid is preferably 2.5% by mass or less, more preferably 2.0% by mass or less, and even more preferably 1.5% by mass or less. It is desirable for the coating to be uniform and wide-ranging. The spray range at a point 50 cm away from the nozzle outlet has a radius of preferably 5 cm or more, more preferably 7.5 cm or more, and even more preferably 10 cm or more.
[0045] The type of atomizing device in the spraying device used in the present invention is not particularly limited. It may be a rotary atomizer type or a nozzle type. In the case of a nozzle type, it may be a one-fluid nozzle or a two-fluid nozzle. It may also be a parallel flow two-fluid nozzle or a fountain type two-fluid nozzle. Among these, it is preferable to use a spraying device equipped with a two-fluid nozzle because it is easy to handle. The Sauter mean particle diameter of the droplets immediately after spraying from the spraying device is preferably 100 μm or less as determined by the phase Doppler method. The smaller the droplets are, the more uniformly the CNF can be attached to the base sheet, so the Sauter mean particle diameter of the droplets is more preferably 80 μm or less, and even more preferably 60 μm or less. The lower limit of the Sauter mean particle diameter of the droplets is not particularly limited, but is, for example, 5 μm or more. The nozzle diameter, air pressure, air flow rate, liquid flow rate, volume ratio of gas to liquid, etc. of the spraying device used are preferably adjusted so that droplets of the above-mentioned Sauter mean particle diameter can be sprayed. For example, in the case of a spraying device using a two-fluid nozzle, it is preferable that the minimum liquid passage diameter is 0.5 mm or more and 2 mm or less, and the volume ratio of gas to liquid (gas:liquid) is 600:1 to 1200:1.
[0046] ·Drying process The substrate sheet after the spraying step is dried. In the manufacturing method of the present invention, the wet coating amount in the spraying step is 0.1 g / m 2 More than 5.0g / m 2 The amount of water used is as little as 100% or less. Therefore, it may be possible for the base sheet after the spraying process to be naturally dried while being transported to the folding process. If natural drying is possible, it is not necessary to introduce a drying device, so it is low cost. If natural drying is not performed during transportation, it is necessary to install a drying device, but since the manufacturing method of the present invention uses a small amount of wet coating, a drying device that consumes little energy is sufficient.
[0047] · Folding process The base sheet after the drying step is folded. The base sheet is folded in either the longitudinal direction or the width direction, or both, while being conveyed. The number of times it is folded and the order in which it is folded in the longitudinal direction and the width direction are not particularly limited. In the manufacturing method of the present invention, the base sheet is folded after a coating liquid containing CNFs having an average fiber length of 450 nm or less is sprayed and dried. The strength of the base sheet is improved due to the uniform adhesion of short fiber CNFs, and therefore, the occurrence of paper breaks during folding can be prevented.
[0048] Other processes The method for producing the wet wipes of the present invention may include the above-mentioned spraying step, drying step, and folding step, and may also include other steps. For example, the method may include a cutting step of cutting the base sheet folded in the folding step. Furthermore, the method may include an impregnation step of impregnating the wet wipes with a chemical solution either before or after the folding step or both, and a packaging step after the impregnation step. The chemical solution to be impregnated may be any known one without any particular limitation, depending on the application of the wet wipes. EXAMPLES
[0049] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0050] Base sheet Non-water degradable non-woven fabric Raw fiber: Rayon / PET = 50 / 50 (mass%) Basis weight: 30g / m 2 Water-degradable nonwoven fabric Raw fiber: NBKP / rayon = 80 / 20 (mass%) Basis weight: 43g / m 2
[0051] <Measurement of carboxyl group amount> 60 mL of a 0.5 mass% aqueous dispersion of carboxylated CNF was prepared. After adding an aqueous 0.1 M hydrochloric acid solution to adjust the pH to 2.5, an aqueous 0.05 N sodium hydroxide solution was added dropwise, and the electrical conductivity was measured until the pH reached 11. The amount of sodium hydroxide consumed (a) in the neutralization stage of the weak acid where the change in electrical conductivity was gentle was calculated using the following formula: Amount of carboxyl groups [mmol / g carboxylated cellulose] = a [mL] × 0.05 / mass of carboxylated cellulose [g].
[0052] <Measurement of average fiber diameter and average fiber length of CNF> A CNF aqueous dispersion diluted so that the concentration of CNF became 0.001 mass% was prepared. This aqueous dispersion was thinly spread on a mica sample stage and heated and dried at 50 °C to prepare a sample for observation. For any 200 of the shape images observed with an atomic force microscope (AFM), the cross-sectional height was measured and averaged to obtain the average fiber diameter. For any 200 of the shape images observed with an atomic force microscope (AFM), using the image analysis software WinROOF (Mitani Trading Co., Ltd.), the fiber length was measured in the range of 10 nm to 2000 nm and averaged to obtain the average fiber length.
[0053] Production Example 1 · Coating liquid 1 (oxidized cellulose nanofiber dispersion liquid 1) 5 kg (bone-dry) of bleached softwood-derived dissolving kraft pulp (Buckeye DKP) was added to 500 L of an aqueous solution containing 78 g (0.5 mol) of TEMPO (Sigma Aldrich) and 755 g (7.4 mol) of sodium bromide, and the mixture was stirred until the pulp was uniformly dispersed. 16 L of 2 M aqueous sodium hypochlorite solution was added to the reaction system, and the pH was adjusted to 10.3 with 0.5 N aqueous hydrochloric acid to start the oxidation reaction (oxidation treatment). The pH in the system decreased during the reaction, but was adjusted to pH 10 by successively adding 0.5 N aqueous sodium hydroxide solution. After reacting for 2 hours, the mixture was filtered with a centrifuge and thoroughly washed with water to obtain carboxylated cellulose. A slurry of carboxylated cellulose was prepared by adjusting the concentration of this to 5.0% (w / v) in water, and hydrogen peroxide was added to this at 2% (w / w) relative to the carboxylated cellulose, and the pH was adjusted to 11.3 with 3 M sodium hydroxide. This slurry was left at 80°C for 2 hours to carry out hydrolysis. This was adjusted to 5.0% (w / v) with water and treated 10 times with an ultra-high pressure homogenizer (20°C, 140 MPa) to obtain carboxylated CNF1. The obtained carboxylated CNF slurry was diluted to 2.5% (w / v) using Homo Disper (Primix Corporation), and this was used as coating liquid 1. The amount of carboxy groups in the obtained carboxylated CNF1 was 1.7 mmol / g, the average fiber diameter was 3 nm, and the average fiber length was 350 nm.
[0054] Manufacturing Example 2 Coating liquid 2 (Oxidized cellulose nanofiber dispersion liquid 2) 5 kg (bone dry) of bleached unbeaten kraft pulp (85% brightness) derived from coniferous trees was added to 500 L of an aqueous solution containing 39 g of TEMPO (Sigma Aldrich) and 514 g of sodium bromide, and the mixture was stirred until the pulp was uniformly dispersed. An aqueous solution of sodium hypochlorite was added to the reaction system to a concentration of 5.5 mmol / g to initiate the oxidation reaction. The pH of the system decreased during the reaction, but 3 M aqueous sodium hydroxide was added successively to adjust the pH to 10. The reaction was terminated when the sodium hypochlorite was consumed and the pH of the system no longer changed. The mixture after the reaction was acidified using hydrochloric acid, filtered with a centrifuge to separate the pulp, and the pulp was thoroughly washed with water to obtain carboxylated cellulose. This was adjusted to 1.0% (w / v) with water and treated three times with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain carboxylated CNF2, which was used as coating liquid 2. The amount of carboxy groups in the obtained carboxylated CNF2 was 1.6 mmol / g, the average fiber diameter was 3 nm, and the average fiber length was 550 nm.
[0055] "Example 1" A sprayer equipped with a two-fluid nozzle as shown below was installed immediately after the long base material roll was unwound from the longitudinal folding processing device equipped with a folding plate. The sprayer was a 150 mm long movable super tube and an external mixing type mini mist nozzle (minimum liquid passage diameter 1.0 mm, air pressure 0.1 MPa to 0.5 MPa, air flow rate 28 to 84 L / min, spray water volume 14 to 292 mL / min) connected to the end of the piping of a high viscosity liquid transport pump with inverter control (Heishin Mono Pump Model NY20, discharge rate 1 to 40 L / min). The conditions of this sprayer were adjusted to spray droplets with a Sauter mean particle size of 45 μm by the phase Doppler method. The coating solution 1 obtained in Production Example 1 was applied to a substrate sheet made of a non-water-decomposable nonwoven fabric in a wet coating amount of 0.1 g / m using this spraying device. 2 (100 mg / m 2 ) and wet sheets were produced for 3 hours at a production speed of 1100 sheets / min. The base paper sheet sprayed with the coating liquid was naturally dried during transportation before reaching the folding process (folding plate). The base sheet could be produced stably without breaking.
[0056] "Comparative Example 1" Wet wipes were produced in the same manner as in Example 1, except that the coating liquid was not sprayed and the production speed was set to 1000 sheets / min. This production speed was the value under conventional production conditions. The base sheet could be produced stably without breaking. "Comparative Example 2" A wet sheet was produced in the same manner as in Example 1, except that the coating liquid was not sprayed. Within an hour of starting production, the base sheet broke, starting from the point of contact with the folding plate during the folding process. "Comparative Example 3" A wet sheet was produced in the same manner as in Example 1, except that Coating Liquid 2 was used instead of Coating Liquid 1. Immediately after the start of production, the spraying was stable, but over time the spraying device became clogged and stable spraying (coating) became impossible. After that, within 2 hours of starting production, the base sheet broke, starting from the point of contact with the folding plate during the folding process.
[0057] "Example 2" Wet wipes were produced in the same manner as in Example 1, except that a water-decomposable nonwoven fabric was used and the production speed was set to 1150 sheets / min. The base sheet could be produced stably without breaking. "Comparative Example 4" A wet sheet was produced in the same manner as in Example 2, except that the coating liquid was not sprayed and the production speed was 1000 sheets / min. The base sheet could be produced stably without breaking. "Comparative Example 5" A wet sheet was produced in the same manner as in Example 2, except that the coating liquid was not sprayed. Within an hour of starting production, the base sheet broke, starting from the point of contact with the folding plate during the folding process.
[0058] [Table 1]
[0059] The manufacturing methods of Examples 1 and 2 of the present invention allowed for stable production of wet wipes without paper breaks. The manufacturing methods of Examples 1 and 2 of the present invention allowed for a production speed 10% or more faster than conventional manufacturing conditions (Comparative Examples 1 and 4). When the production speed was increased without spraying CNF, paper breaks occurred (Comparative Examples 2 and 5). The manufacturing methods of Examples 1 and 2 of the present invention allowed for stable spraying (coating) with less clogging of the spraying device than when the cellulose nanofibers used were long fibers (Comparative Example 3).
Claims
1. A coating liquid containing 0.1% by mass to 3.0% by mass of cellulose nanofibers with an average fiber length of 450 nm or less is applied to a long substrate sheet in a wet coating amount of 0.1 g / m 2 5.0g / m or more 2 A spraying step of spraying the following: a drying step of drying the base sheet after the spraying step; A folding process step of folding the base sheet after the drying process; A method for producing a wet wipe, comprising the steps of:
2. 2. The method for producing wet wipes according to claim 1, wherein the base sheet is a nonwoven fabric.
3. 2. The method for producing wet wipes according to claim 1, wherein the drying is natural drying.
4. The method for producing a wet sheet according to any one of claims 1 to 3, characterized in that the cellulose nanofibers are oxidized cellulose nanofibers.
Citation Information
Patent Citations
Method for producing nonwoven fabric sheet
JP2017115262A